Discovery of Novel Host Molecular Factors Underlying HBV/HCV Infection - Huang, Xubo; Glessner, Joseph T.; Huang, Jinxia; Zhou, Desheng; March, Michael E.; Wang, Hongna; Xia, Qianghua; Hakonarson, Hakon; Li, Jin (Frontiers in Cell and Developmental Biology, 2021)
Hepatitis is an inflammatory condition of the liver which is frequently caused by the infection of hepatitis virus B (HBV) or hepatitis virus C (HCV). Hepatitis can lead to the development of chronic complications including cancer, making it a major public health burden. Co-infection of HBV and HCV can result in faster disease progression. Therefore, it is important to identify shared genetic susceptibility loci for HBV and HCV infection to further understand the underlying mechanism. Through a meta-analysis based on genome-wide association summary statistics of HBV and HCV infection, we found one novel locus in the Asian population and two novel loci in the European population. By functional annotation based on multi-omics data, we identified the likely target genes at each novel locus, such as HMGB1 and ATF3 which play a critical role in autophagy and immune response to virus. By re-analyzing a microarray dataset from Hmgb1-/- mice and RNA-seq data from mouse liver tissue overexpressing ATF3, we found that differential expression of autophagy, immune and metabolic gene pathways underlie these conditions. Our study reveals novel common susceptibility loci to HBV and HCV infection, supporting their role in linking autophagy signaling and immune response.